Wyobrażenie młodych dorosłych o szczęściu rodzinnym - Lisiecka-Bednarczyk, Agnieszka (Kultura-Społeczeństwo-Edukacja, 2024)
The sense of satisfaction with one’s family life is defined as a component of mental well-being. Giving happiness to a loved one, your child and feeling happiness in close relationships allows for better professional functioning, general human development, and even a positive impact of family well-being on human health is indicated. The proposed article is a presentation of research results and analyzes regarding the preparation of young adults to start a family. The aim of the research was to learn about young adults’ ideas about family happiness and their assessment of marriage and parenthood. The direction of the research was determined by the following research problems: 1. What are the attitudes of young adults towards marriage and parenthood? 2. According to the surveyed young adults, what competences allow you to build a happy relationship/marriage? 3. How do the respondents assess their preparation to start a family? The research method used was a semi-structured interview conducted using an anonymous questionnaire containing open questions. The sample selection was non-probability, based on the availability of respondents. The research was conducted from January to September 2023. The analysis of the research material was carried out using interpretive phenomenological analysis. The study involved 69 young adults, 60 women and 9 men. These people can be presented as representatives of the previously described Generation Z. The work indicates the resources and factors that, according to young adults, will allow them to feel family happiness, despite the crisis of family, marriage and parenthood that is observed today. The research can be an inspiration to construct research tools and conduct research on the quality of relationships, building relationships or preparing contemporary youth and young adults to start a family.